THE DIFFERENCE OF STUDENTS MOTIVATION TOFINISH THESIS BASED ON THEIR LIVING PLACE - Ida Tri Wahyuningsih; Anita Listiara (Jurnal EMPATI, 2013)
This study aims to know the difference of students motivation to finish thesis who live with parents and who live without parents.The subjects were students of Computer Science Faculty of Dian Nuswantoro University who taking course of thesis. The subjects were 60 students, with the distribution of 41 students who live with parents and 19 students who live without parents. Retrieval of data using scale of motivation to finish the thesis that consist 50 items (α = 0,938).Analyzing data usingMann-Whitney Test, z value  = -0.684 and p = 0,494 (p > 0,05). In other words, there is no difference in motivationto finish thesis between students who live with parents and who live without parents.